Оцінка впливу глобальних змін клімату на кількість та нерівномірність опадів у Карпатському регіоні - Волошкіна, О.С.; Цікало, О.В. (Екологічна безпека та природокористування, 2012)
Based on the analysis of monitoring data monthly observations of air temperature and rainfall in four the main rivers basins of posts in the region (posts of "Drohobych", "Yampol" on the river Dniester, post "Kolomyia" basin of the Prut River, the post "Chortkiv" Siret river basin) built correlation relationship between these factors to allow you to do prognosis the future and assign environmental measures in river basins.